(untitled) (Journal of Pharmaceutical Negative Results, 2022)
At most BCG vaccination in childhood is being finalized with scar formation. Absence of BCG scar formation few days post-vaccination can be a state of anergy. Though, gradual scar fade up may demonstrate a case of waning immunity. The present work was performed onto three groups of healthy children. Scar bearing BCG vaccinee child, non-scar bearing BCG vaccinee child and non-vaccinated child as controls. Age, scar size and macrophage inhibitory factor MIF cytokines were determined. A fraction of scar bearing BCG vaccinee were showing lower MIF concentration than normal controls. A state of waning cytokine responses in spite of the presence of scar. Likewise, a fraction of non-scar bearing BCG vaccinee were showing MIF concentrations lower than that of normal healthy controls ,a state of waning cytokine responses that parallels the waning of gross manifestation of the scar reactions. These findings point out the condition of heterogeneity or divergency of the immune response to BCG vaccines in childhood. MIF cytokine herd response were showing low moderate, and high responders in vaccinated children. The MIF cytokine herd response plots were of Gaussian distribution plots.